PENERAPAN TEORI OPERANT CONDITIONING DALAM MENINGKATKAN MOTIVASI MENGHAFAL Al-QUR’AN SANTRI DI LPTQ DARUL IMAM MASJID AGUNG - Syarifah Huriyah; Ahdad, Muhammad M; Rahman, Ulfiani (Indonesian Journal of Islamic and Social Science, 2023)
Recently, many Al-Qur'an memorization programs have appeared which are implemented in Islamic boarding schools, but they do not yet have the right formula for implementing these programs. This study aims to examine in depth the application of operant conditioning theory to increase students' motivation to memorize the Al-Qur'an at LPTQ Darul Imam Masjid Agung Sidrap. This study uses a qualitative approach, with data sources from badals (teachers) and students. Collecting data using observation, interviews, and documentation. The data obtained from the results of the interviews will then be analyzed qualitatively using data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of the study showed that students at LPTQ Darul Imam Masjid Agung Sidrap memorized the Qur'an every day starting after subuh prayer, after dhuha, after asr, and isya prayer. The memorization method applied is the Ziyadah and Murajaah memorization methods. The theory of operant conditioning that is applied to increase students' motivation to memorize is to provide rewards and punishments.